Anti-sickling activities of two isolated compounds from the root of Combretum racemosum P. beauv. (Combretaceae) (2021)
Ethnopharmacological relevance: Evaluation of plants such as Combretum racemosum with claimed traditional use in the management of sickle cell anaemia in Nigeria and other parts of West Africa could serve as a useful research strategy in the search for potential anti-sickling drugs and templates. Aim of the study: This study aimed at evaluating the antisickling potential of C. racemosum by activity-guided purification and isolation of its active constituents. Materials and methods: Crude methanol extract of the root of C. racemosum and the fractions obtained by par titioning with chloroform, ethyl acetate, and aqueous were investigated for anti-sickling activity against sodium metabisulphite induced sickling of sickle cell haemoglobin (HbSS). Repeated chromatographic separations were conducted on the most active chloroform fraction to purify and isolate bioactive compounds for further tests for anti-sickling activity. The characterization of the isolated compounds was done by mass spectrometry (FD+MS) and nuclear magnetic resonance ( 1 HNMR) spectroscopy. Results: The chloroform fraction (FA) (% sickled erythrocyte ranged from 3.0 to 34.1) exhibited better anti sickling activity than aqueous (% sickled erythrocyte ranged from 38.9 to 51.5) as well as the crude methanol (% sickled erythrocyte ranged from 19.1 to 30.4). Hence, the phytochemical investigation was focused on the chloroform fraction, which led to the identification of two ellagic acid derivatives (3,3′ ,4′ -tri-O-methyl ellagic acid (A) and 3,3′ -di-O- methyl ellagic acid (B). The two isolated compounds possessed good, comparable anti sickling activities with compound A exhibiting a slightly better in vitro activity. Conclusion: This paper reports for the first time anti-sickling principles from C. racemosum and therefore, provided some justification for the ethnomedicinal use of the plant in the management of sickle cell disease.